KERANGKA PENILAIAN LIFE-CYCLE COST UNTUK PROYEK PEMELIHARAAN JALAN NASIONAL MENGGUNAKAN KONTRAK BERBASIS KINERJA - Susanti, Betty; Wirahadikusumah, Reini D. (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Performance Based Contract (PBC) is one strategy to improve the effectiveness of road maintenance. PBC recently applied in Indonesia in 2011 and driven by Performance-Based Budgeting system. Through this budgeting system, expenditures for national road maintenance projects should be carried out as efficiently as possible and provide a long service life. But the national road agency still do not have an instrument that can be used to assess the efficiency of road maintenance costs for the project which will be delivered using PBC approach. Appropriate method used to assess the life cycle cost (LCC) efficiency of an infrastructure asset is using Life Cycle Cost Analysis (LCCA).This study aims to develop an assessment framework to specifically assess LCC for road maintenance project which will be contracted usingPBC schemes. LCC assessment framework generated in this study takes into account the road agencies and road users cost, with input variables consist of road design, LCCA analysis period, the road performance prediction, and the road maintenance strategies.